APPLICATION OF LEARNING CELL STRATEGY TO IMPROVE POSING QUESTION IN SOCIAL STUDIES - Nurul Hidayati; Siti Wahyuningsih; Hadiyah Hadiyah (Universitas Sebelas Maret, 2018)
The purpose of this research is to improve the posing questions on social studies of third grade students elementary school. Methods of data retrieval is done by observation, interview, and documentation. Data collected are result of posing question observation, result of teacher and students interview and documentation of learning process. Data validity used are validity of content and triangulation of sources and methods. Data analysis using interactive models. The result of research is quantity of question in cycle I and cycle II in sequence that is 444 and 455 questions. The number of questioning students increased to 100% of students in the class or a total of 36 students. The quality of the questions indicated includes the cognitive thinking levels C1, C2, C3, and C4, whereas the dimensions of knowledge lie in the factual, conceptual, procedural, and metacognitive. Based on the results of research can be concluded that the application of learning cell strategy can improve the posing question